Analysis and testing methodology For bluetooth audio in 0km/field Claimed products of BOSCH CAR MULTIMEDIA PORTUGAL, S.A. - Marimuthu, Aravind (2017)
The main intension of the project is to develop and implement a standard test setup and automatic testing scripts to test the Bluetooth module’s audio of the 0KM/Field claimed products of Bosch Car Multimedia Portugal, S.A. 0KM/Field claimed products are the products claimed by the automobile companies as malfunctioning before going to the final customers. The work developed in the QMM-FA (Quality Management & Methods – Failure Analysis) department will be used for testing the characteristics of the Bluetooth module’s audio to enabling answering the customer’s queries as quickly as possible and in a standard way. Currently testing of Bluetooth modules is achieved by using the mobile phones in the customer mode. Customer mode means that this test is simulates a typical customer scenario and does not follow any internal testing specifications of Bosch. Tests strongly depends on external sources (Mobile phones). Basically, two types of tests are required to evaluate the quality of the CM products: one is testing and measurement of the characteristics of the products and another one is functional tests. The functional tests are carried out by using mobile phones and QMM-FA is already performing a functional test. The proposed testing setup is framed by using R&S Audio Analyzer – UPL, R&S Signal Generator, R&S Programmable Power Supply and Bosch BLAUBOX and BLAUKIT. This setup is mainly used to test the audio streaming and other characteristic of the BT module’s audio. Bosch having a diverse variety of CM products maximum of the products are having a Bluetooth module. The developed test plan was implemented in the “NISSAN A IVI SCOPE_1” product. Test script was developed using blk programming codes in BLAUKIT (Bosch’s internal platform). All the used equipment are connected through GPIB connector to configure & acquire remotely. Notion of this proposed test plan will be the same for all the other 0KM/Field claimed products, only the testing variables and the way of communication with the product’s modules are different depends on the product’s specification. Bosch standards and specifications are framed according to the customer specification of each product. For “NISSAN A IVI SCOPE_1” product, Bosch Groups already having a set of requirements from the NISSAN Group of companies. In Bosch manufacturing plant, manufactured products should accomplish the customer requirements. This test setup is framed to test the BT module’s audio according to the Bosch testing standards and specifications to ensure the quality and functionality of the Bluetooth audio of “NISSAN A IVI SCOPE_1” product. By using the proposed test plan it enables the claimed product test and analysis the characteristics of the Bluetooth Audio in the stipulated time with automatic testing.